Skin Carotenoid Levels Over Time and Differences by Age, Sex, and Race Among Head Start Children (3-5 years) Living in Eastern North Carolina - Burkholder, Sarah (East Carolina University)
Objective: Examine differences in skin carotenoid levels (SCL) based on time, age, sex, and race of preschool-aged children (PSAC) enrolled in Head Start (HS) in North Carolina (NC). Design: Data were collected using surveys from participating families. PSAC's SCL were measured 3 times over a 6-month period. Setting: 3 HS centers in NC Participants: 112 children aged 3-5 years old, enrolled in HS Main Outcome Measure(s): Differences in SCL assessed using the Veggie Meter[registered] based on time, sex, race, and age Analysis: Analysis of Variance (ANOVA) with a Greenhouse-Geisser correction to assess SCL at Time 1 between sex, race, and age (n=112). Repeated measures ANOVA to assess SCL over time (n=45) using Bonferroni correction(b). Results: On average, children were 4 years old, African American (81.3%), male (57%) and mean SCL 266 (SD 82.9). SCL were significantly different over time (p[less-than].001). Significant differences were observed between ages (p=.01) and sex (p=.01), but not between race. Conclusions and Implications: The Veggie Meter[registered] is a promising tool to assess fruit and vegetable intake but needs to be validated in PSAC as has in adults. Sex, age, and race are potential confounders which should be assessed in future studies using the Veggie Meter[registered].
Keywords: Skin Carotenoid Levels; Preschool Aged Children; Head Start; Veggie Meter®; Carotenoids; Skin; North Carolina